Digital Pre-Emphasis Compensator for Loudspeaker on the Inverse Parallel Hammerstein Model - R. Z. Akhmetsafina (Известия высших учебных заведений России: Радиоэлектроника, 2016)
Models of nonlinear compensators for decreasing total harmonic distortions of loud-speakers are considered. Digital linearization is suggested as a diagram with internal feedback based on the inverse parallel Hammerstein model.